Proceedings of the 51st Hawaii International Conference on System Sciences 2018
DOI: 10.24251/hicss.2018.654
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Discontinuing Knowledge Work Automation - Surfacing of Deskilling Effects and Methods of Recovery

Abstract: IS automation pervades business processes today. Thus, concerns have been raised about automation's potential deskilling effects on knowledge workers. We conduct a revelatory case study about an IT service firm where a managerial decision was taken to discontinue a fixed assets management (FAM) software that provided seemingly effective automation of fixed assets accounting and reporting. We study how automation can result in latent deskilling that later becomes apparent when the system gets discontinued, caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Key vulnerabilities faced by domain experts relate to professional knowledge, skills, identity, and reputation. For example, research suggests that automation through AI may lead to deskilling [67,68]. A related vulnerability stemming from the AI explanability challenge is the ability of the domain expert to understand the AI system and be able to explain and justify decisions to other stakeholders, particularly when AI system outputs are used in service delivery (e.g.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Key vulnerabilities faced by domain experts relate to professional knowledge, skills, identity, and reputation. For example, research suggests that automation through AI may lead to deskilling [67,68]. A related vulnerability stemming from the AI explanability challenge is the ability of the domain expert to understand the AI system and be able to explain and justify decisions to other stakeholders, particularly when AI system outputs are used in service delivery (e.g.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…A concern related to automated AI is the potential for deskilling if domain experts over-rely on automated systems [67,68]. One study found financial investors trust fully automated artificial advisors more than human advisors [69].…”
Section: Automation Versus Augmentationmentioning
confidence: 99%
“…One societal challenge is how education is changing due to the introduction of these robots, either in factories or in hospitals where the surgery success does not depend just on the surgeon any longer but on the complex interaction and interplay between the doctor, the supporting staff, and the robot (i.e., the manufacturer) (Yang et al, 2017). Latent deskilling has to do with the gradual loss of essential skills due to overreliance on AI and workplace robotics (Rinta-Kahila et al, 2018). That becomes more apparent when a workplace process or a specific product is discontinued, and it may cause severe disruptions in workers' daily work and internal organizational processes.…”
Section: Societal Dimensionmentioning
confidence: 99%
“…Similarly, implementing artificial intelligence to substitute human loan consultants' tasks and responsibilities in a bank alleviated the consultants' work pressures but at the same time the resultant loss of autonomy negatively disrupted their role identities (Mayer et al, 2020;Strich et al, 2021). The employees' fears of losing their professional statuses were warranted -systems that improve processes by automating analysis and decision-making have been found to gradually erode their users' expertise (Dowling et al, 2008;Rinta-Kahila et al, 2018;Sutton et al, 2018).…”
Section: Negative Unintended Consequences and Destructive Systemsmentioning
confidence: 99%